1996
DOI: 10.1017/s0031182000066269
|View full text |Cite
|
Sign up to set email alerts
|

Induction of changes in human behaviour by the parasitic protozoanToxoplasma gondii

Abstract: Toxoplasma gondii, the coccidian parasite, is known to induce changes in the behaviour of its intermediate hosts. The high prevalence of this parasite in the human population (20-80%) offers the opportunity of studying the influence of the parasite on human behaviour by screening of a normal population. A total of 224 men and 170 women were tested for toxoplasmosis and their personality profiles were measured by Cattell's questionnaire. Highly significant differences between Toxoplasma-infected and uninfected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
106
0
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(116 citation statements)
references
References 23 publications
5
106
0
4
Order By: Relevance
“…In male LongEvans rats, Latent Toxoplasma infection resulted to reduced the normal aversion to cat odor and converted it into a mild attraction (Vyas et al 2007). Flegr et al (1996) reported personality profiles such as, superego strength (the willingness to accept group moral standards) were significantly different between Toxoplasma-infected and uninfected subjects. In a populationbased study, association of Toxoplasma-specific immunoglobulin G results with mood disorder outcomes in 7,440 respondents was assessed.…”
Section: Discussionmentioning
confidence: 95%
“…In male LongEvans rats, Latent Toxoplasma infection resulted to reduced the normal aversion to cat odor and converted it into a mild attraction (Vyas et al 2007). Flegr et al (1996) reported personality profiles such as, superego strength (the willingness to accept group moral standards) were significantly different between Toxoplasma-infected and uninfected subjects. In a populationbased study, association of Toxoplasma-specific immunoglobulin G results with mood disorder outcomes in 7,440 respondents was assessed.…”
Section: Discussionmentioning
confidence: 95%
“…Results showed that differences probably exist in the weight of Toxoplasma-negative and Toxoplasma-positive women (see the first row of Table 2). The effect of latent toxoplasmosis can be expected to increase with the length of Toxoplasma infection (Flegr et al 1996. The moment of Toxoplasma infection is usually not known for most subjects with latent toxoplasmosis.…”
Section: Resultsmentioning
confidence: 99%
“…However, despite an extremely high prevalence of this form of toxoplasmosis in many countries, only minimal attention is paid to the study of its potential impact on human health (Holliman 1997). Certain studies demonstrate possible correlation of latent toxoplasmosis with some types of brain tumours (Ryan et al 1993) or with specific changes in personality profiles of infected subjects (Flegr et al 1996, 2003, Flegr and Havlíček 1999. Our results, namely, decreased body weight of Toxoplasma-positive pregnant women (and possibly also decreased growth rate of the foetus), suggest that latent toxoplasmosis might in some way negatively affect the health of infected subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Les résultats des modèles murins d'infection latente ont encouragé la recherche de corrélats comportementaux à l'infection latente chez l'homme. Ainsi des études cliniques ont trouvé des profils de personnalité différents entre les sujets présentant une infection latente et les sujets sains [30]. D'autres études ont aussi montré un quotient intellectuel plus faible chez les sujets infectés [31], ou encore des performances psychomotrices altérées [32].…”
Section: Infection Par Toxoplasma Gondii Et Modifications Du Comporteunclassified